An innovative solid state manufacturing approach for developing high performance Al/Cu bimetals. (November 2022) - Prathyusha, B.; Dhal, A.; Panigrahi, S.K.
Abstract: Al/Cu bimetals are extensively used in various sectors like electronics and electrical, cookware and decorative industries to make parts and components. The bimetallic components developed by most of the existing manufacturing processes often shows both poor interfacial bond strength and inferior tensile strength. The present work explores an alternate microstructural engineering based novel manufacturing approach to improve the product performance of Al/Cu bimetals via a hybrid manufacturing process consisting of: (a) cryorolling + short-term annealing to engineer microstructural variation in parent materials and (b) laboratory plane strain bonding process for joining/bonding. Four different microstructural combinations are engineered in Al and Cu parent materials (such as ultrafine grained, bimodal/heterogeneous grained, fine grained and coarse-grained microstructures) and the influence of such microstructural combinations on joining potential of Al/Cu bimetals at wide range of process parameters are established. Among all microstructural combinations, ultrafine grained Al + bimodal grained Cu combination has shown excellent bond quality due to dual advantage of high ductility from its coarse-grained counterparts and interfacial strain localization from the UFG counterparts. When deformed at high deformation speed, the bimodal material shows signatures of excellent bonding in the form of microscopic waves and swirls. A possible mechanism is cyclic interaction between the back stress and forward stress arising due to the differences in the strain accommodation capabilities between the fine and coarse grains in this microstructure. This cyclic strain provides a ratcheting effect which results in exceptionally high shear strain at interface and facilitates enhanced bond quality due to wave-like material interlocking. Fine element simulations are also in agreement with experimental results when upscaled to industry scale roll bonding process.